Analisis Keluhan Tamu terhadap Kualitas Layanan Housekeeping melalui Google Review: Studi Kasus Hotel Tentrem Yogyakarta - Vindra Akbar Jati Kusuma; Octaviani Gita Putri; Emmelia Nadira Satiti (Tamasya : Jurnal Pariwisata Indonesia, 2025)
The 5-star hotel is full of beauty, futuristic design, and perfect service. One of the components that guests complain about at the Tentrem Hotel Yogyakarta is housekeeping negligence. The research method is qualitative, with data collection techniques including interviews, observations, and documentation. The results of the study show that the forms of negligence that occur in housekeeping services at Hotel Tentrem Yogyakarta are 3 (three) actions: first, negligence in cleaning guest rooms, errors in placing guests' personal belongings, and delays in providing additional requests (amenity delay). Housekeeping negligence affects guest satisfaction at Hotel Tentrem Yogyakarta by reducing the reliability and tangibles dimensions of service quality. Guests feel the hotel cannot be trusted to provide a comfortable stay experience, leading to a decrease in the empathy and assurance dimensions. Guests feel their privacy is violated, which may even lead to suspicion toward hotel staff. Efforts to improve the negligence occurring in housekeeping services at Hotel Tentrem Yogyakarta involve three actions: implementing an inspection checklist and supervisor verification before guests check-in, ensuring staff are well-trained, educated, and professional in their work, and adopting a digital logistics system to record guest requests and prioritize deliveries.